The apothecary diaries. Volume 7 - Hyūga, Natsu (Square Enix Manga, 2022)
"Proving herself indispensable yet again by saving Jinshi from a horrific fate. Maomao is given the chance to explain her rash behavior during the holy ritual. But when she continues her investigation into the foiled plot, a bizarre outcome awaits, leaving the plucky apothecary impressed by the sheer nerve of the culprit behind it. But admiring the exploits of another won't get Maomao very far when Jinshi tasks her with a feat of her own-- to present him with blue roses at the needling of the eccentric La Kan! How will Maomao respond to this provocation from the man she despises the most?"